Estrategias pedagógica y su incidencia en el aprendizaje de la asignatura de comercio y administración de los estudiantes del tercer año de bachillerato de la Unidad Educativa Particular República del Ecuador, del Cantón Quevedo, Provincia de los Ríos, periodo 2015 - 2016 - Vera Lagua, Betty Alexandra (2015)
More and more teachers are already using new and innovative teaching strategies which impact the learning of the subject of Business and Management. However, many of them are not aware of the techniques they are using, because by not explicitly identify the learning strategies they use, can empower students to use these strategies misleadingly and in a wider context. Highlighting and present learning strategies through this research, it is intended to illustrate the skills of teachers and students in a real context. When explicitly it teaches teaching strategies, which share responsibility for student learning with students themselves. Students assume greater responsibility for their own learning and gain greater independence. This is known as the student-centered approach to instruction. It is characterized by a focus on how students learn, explicit instruction in learning strategies, setting explicit goals of the students themselves, and improved academic performance. Learning instructional strategies requires us to consider not only what we do to teach effectively what our students to facilitate their own learning, as in the case of the implementation of educational strategies and how it affects the learning process the course of business and management students of the third year of high school at the Private Education Unit "Republic of Ecuador", the Canton Quevedo, province of Los Rios, period 2015 - 2016